Amphibians and reptiles of Bohol Island, The Philippines: The herpetofauna of Rajah Sikatuna Protected Landscape (Journal of Biodiversity Conservation and Bioresource Management, 2025)
This study conducted from August to October 2019 at Rajah Sikatuna Protected Landscape (RSPL), Bohol, The Philippines, recorded a total of forty-two (42) herpetofauna species, of which 18 were amphibians (one toad and 17 frogs), and 24 were reptiles (11 snakes and 13 lizards). Including the data from other research conducted on the island of Bohol, our records had a total of 54 cumulatively; Twenty-four (24) of which are Philippine endemics, with one species (Philautus sp.) inhabiting the forest limestone of RSPL. Despite the extensive sampling effort in this study, there were some species that were not observed but recorded in other literature. Most of the reptilian species recorded were new species. This survey also revealed that the forest areas of Bohol inhabit eight species of herpetofauna, which are categorized as threatened and vulnerable. Compared to other islands in Central Visayas, this study found a smaller but similar number of species that would merit further taxonomic studies like gene sequencing and DNA barcoding. With these findings, RSPL could be a possible herpetofauna diversity hotspot on Bohol Island, and conservation of these resources should be continuously implemented.J. biodivers. conserv. bioresour. manag. 10(2), 2024: 31-48